Mantra Agama: Islamic Dialectics and Local Beliefs of The Suku Anak Dalam Jambi - Eli Sapina; Arfan Arfan; Abdul Halim; Zaki Mubarak; Mohd Kailani (Jurnal Studi Agama, 2022)
This study examines the dialectics of local beliefs and religions in the form of mantras in the Suku Anak Dalam that are difficult to abandon and are still practiced even though they have embraced their new religion (Islam). This research uses a descriptive quality method by taking a location in the Suku Anak Dalam community in Pasir Putih Jambi Village. Data were obtained through interviews, observations, and documentation. The results of this study found that the Jambi Suku Anak Dalam had animist beliefs in their pre-Islamic lives, expressed by mantras in aspects of their lives. After they embraced Islam, the old beliefs they held were not completely abandoned by them. The mantras as expressions of their old beliefs were then elaborated with Islamic teachings in the form of putting basmalah utterances at the beginning of their mantras and replacing the gods with the Lord Allah as the place of asking in the mantras.